2020
DOI: 10.3389/fvets.2020.00241
|View full text |Cite|
|
Sign up to set email alerts
|

Craniomaxillofacial Trauma in Dogs—Part I: Fracture Location, Morphology and Etiology

Abstract: Treatment of craniomaxillofacial (CMF) trauma in dogs often requires a multidisciplinary approach and a thorough understanding of the CMF skeletal structures involved. The aim of this retrospective study was to use a large number of CT studies of dogs evaluated for CMF trauma and to describe fracture location and morphology in relation to demographic data and trauma etiology. The medical records and CT studies of 165 dogs over a 10-year period were evaluated. The skeletal location of CMF fractures as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 32 publications
4
26
0
Order By: Relevance
“…The overarching goal of this and similar studies is to identify instances where MRI can be used in lieu of CT to provide adequate concurrent assessment of traumatic brain injuries and associated fractures of the cranial vault. Despite the good diagnostic performance of MRI in facial fracture assessment in this study, CT will likely remain the gold standard for imaging of animals with maxillofacial trauma, especially when planning surgical interventions (38,39). MRI had least agreement with CT in the detection of TMJ fractures.…”
Section: Discussionmentioning
confidence: 78%
“…The overarching goal of this and similar studies is to identify instances where MRI can be used in lieu of CT to provide adequate concurrent assessment of traumatic brain injuries and associated fractures of the cranial vault. Despite the good diagnostic performance of MRI in facial fracture assessment in this study, CT will likely remain the gold standard for imaging of animals with maxillofacial trauma, especially when planning surgical interventions (38,39). MRI had least agreement with CT in the detection of TMJ fractures.…”
Section: Discussionmentioning
confidence: 78%
“…All methods relating to case selection, image acquisition, fracture evaluation, and categorization of demographic and traumarelated data were previously described in Part I of this study and are repeated below. All figures referenced in this Methods section appear in Part I of the accompanying paper (9).…”
Section: Methodsmentioning
confidence: 99%
“…In Part I, we demonstrated that trauma etiology is associated with fracture location (9). Similarly, fracture morphology can also vary based on the location of the fracture.…”
Section: Introductionmentioning
confidence: 92%
“…The diagnostic yield of CT is greater than that of radiography for the identification of fracture morphology in the craniomaxillofacial region that is particularly useful for surgical planning. 22 This is especially true for cases with breedassociated, dental overcrowding and a class III malocclusion, 23 such as the subject of this report. Furthermore, CT allowed for easier identification of the three unerupted first premolar teeth and examination of the fracture ends for underlying pathology.…”
Section: Discussionmentioning
confidence: 83%